Evaluation of Clinical Pathway Implementation in Pneumonia Cases in the Internal Medicine Inpatient Unit at Risa Sentra Sentra Medika Hospital, Mataram with the Integrated Care Pathway Appraisal Tool (ICPAT) Method - Nurdin, Findy Wijaya; Purwadhi, Purwadhi; Agung, Ign Wiseto (Journal of Health Policy and Management, 2023)
Background: In the health insurance system, there are 2 main pillars, namely service quality and financing control. The quality of health services can be identified by measuring the suitability of the service with the agreed clinical pathway. Data from SEAMIC Health Statistics 2011 shows that pneumonia is the 6th cause of death in Indonesia, therefore a good quality clinical pathway is needed. Integrated Care Pathway Appraisal Tool (ICPAT) is one of the instruments that has been validated and can be used to evaluate the content and quality of ICP.Subjects and Method: Study design using qualitative methods and with a case study research design. Population: quantitative data population from all medical records, qualitative data population the researchers involved all officers involved in implementing the clinical pathways. Instrument: List of questions to evaluate the implementation of the use of clinical pathways and ICPAT. Validity: with triangulation techniques. Outcome: compliance assess-ment and recommendations for improvement to maintain quality. Results: Input Aspect, In Dimension 1 What are the Correct Clinical Pathways? it the percentage content was 50%, and the quality was 50%. Dimension 6 (Organizational Role?) in the CP content value is 100% and the quality is 58%. Process aspect, Dimension 2 (Clinical Pathway Documentation Process) CP documentation process in terms of content is 30.43% and quality is 25%. Dimension 3 (Clinical Pathway Development Process) the content is 61.54% and the quality is 41.18%. Dimension 4 (Clinical Pathway Implementation Process) the percentage of content is 60% and the quality is 100%. Dimension 5 (Maintenance Process of clinical pathways) the percentage of the content is 25% and the quality is 38.46%. Aspects of Output Those who comply with using the clinical pathway are 0 (0%), meaning that no one is compliant in using the clinical pathway.Conclusion: CP Pneumonia at Risa Sentra Medika Hospital complies with the ICPAT assessment standards but the quality and content only meet less than 50% based on the aspects assessedKeywords: clinical pathway, pneumonia cases, ICPAT assessment.Correspondence: Findy Wijaya Nurdin. Universitas Adhirajasa Reswara Sanjaya. Ransiki Kota, Kabupaten Manokwari Selatan. Email: Findwijaya@gmail.com. Mobile : +62 81242866438.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.01.04